NOTARY - PERFORMS THE DUTIES OF MEDIATOR FOR DISPUTES - B. Sh. Khodjaeva,; U. R. Mukhtorov, (Galaxy International Interdisciplinary Research Journal, 2023)
Consistent work is being done in the country to improve communication between state bodies and citizens, to ensure reliable protection of citizens' rights and freedoms, and to introduce modern mechanisms for solving their problems.